THE EFFECT OF STUDENT TEAM ACHIEVEMENT DIVISION (STAD) STRATEGY ON THE ABILITY OF THE SECOND YEAR STUDENTS OF SMPN 1 SIAK KECIL IN COMPREHENDING RECOUNT TEXTS - Agmaliza Sabrina; Eliwarti Eliwarti; Fakhri Ras (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This pre-experimental research used One-Group PretestPosttest design to find out whether or not there is a significant effect of using Student Team Achievement Division (STAD) strategy on the ability of the second year students of SMPN 1 Siak Kecil in comprehending recount texts. The sample of the research was 27 students of class VIII-2 and obtained by using cluster random sampling technique. The data collected by giving a pre-test to see the student’s reading ability in comprehending recount texts before the treatment and continued by giving a post-test after the treatment. Then, the results of the tests were compared. The result of the data analysis showed that mean score of the pre-test was 65.22 and the mean score of the post-test was 75.51. In other words, the mean score of the post-test is higher than the pre-test, that is as this as 10.29. The value of t-obs was higher than t-table (12.108 > 2.055) at significant level of 5%. It can be concluded that Alternative Hypothesis (Ha) is accepted. Hence, there was a significant effect of Student Team Achievement Division (STAD) strategy on the ability of the second year students of SMPN 1 Siak Kecil in comprehending recount texts. The implication of the findings was that students’ reading ability could be improved through the application of STAD strategy. The strategy could also help students to be confident and active in reading classroom activities.Key Words: Effect, Student Team Achievement Division (STAD) Strategy, Recount Texts.